Forensic psychology reconsidered: a critique of mental illness and the courts - Polizzi, David (Routledge, 2016)
Introduction to forensic psychology -- The social construction of mental illness and the law -- From the asylum to the penitentiary: a historical perspective -- Competency to stand trial (CST) -- Other types of legal competencies -- Criminal responsibility: state of mind at the time of the crime and the insanity -- Defense -- Coerced treatment, medication, and mental health courts -- Drug courts -- Eyewitness memory -- Closing reflections